Foreign Direct Investment and the Profitability of Domestic Firms: Panel Data Evidence from the UK Manufacturing Industry - Anyadike, Kossy (Kosisochukwu) (2007)
This paper highlights the effects of foreign direct investment (FDI) on the profitability of domestic firms in the UK Manufacturing industry. The Manufacturing sector in the UK is of interest to me due to the declining number of output in this sector (CBI report 2006). A report by Julian Smith (n.d) indicates that the level of competitiveness in global markets has become increasingly hard for the UK manufacturing industry to maintain over the last decade. As a result, the level of profitability for shareholders and for capital reinvestment could be affected. The purpose of this paper is to empirically examine whether FDI affects the profitability of domestic firms, using data from the UK manufacturing sector. I have chosen to study on this topic because I would like to understand how foreign direct investments affect domestic firms especially with regards to profitability.